2004
DOI: 10.1097/01.aog.0000124571.04890.67
|View full text |Cite
|
Sign up to set email alerts
|

Are Children Born After Assisted Reproductive Technology at Increased Risk for Adverse Health Outcomes?

Abstract: As assisted reproductive technologies (ARTs) are increasingly used to overcome infertility, there is concern about the health of the children conceived. The empirical evidence for associations with outcomes related to child health is variable and should be evaluated with consideration of methodological shortcomings. Currently, there is convincing evidence that ART treatment may increase the risk of a few outcomes. Experimental laboratory studies document that various constituents in culture media affect variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
88
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(93 citation statements)
references
References 60 publications
1
88
1
3
Order By: Relevance
“…The titles and the abstracts of the papers were screened independently by two experts, and 161 articles which contained information on both short-and long-term health outcomes of children born after ART were selected. Citation indices, bibliographies of the articles and review papers (Brinton et al, 2004;Schieve et al, 2004;Lightfoot et al, 2005) were also checked to complete the search. We selected a total of 14 studies that met the inclusion criteria for the meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The titles and the abstracts of the papers were screened independently by two experts, and 161 articles which contained information on both short-and long-term health outcomes of children born after ART were selected. Citation indices, bibliographies of the articles and review papers (Brinton et al, 2004;Schieve et al, 2004;Lightfoot et al, 2005) were also checked to complete the search. We selected a total of 14 studies that met the inclusion criteria for the meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Most papers on the consequences of ART concentrated on short-term outcomes, such as perinatal mortality, multiple pregnancies, weight at birth and malformations (reviewed in Schieve et al, 2004 andHansen et al, 2005), while few studies have considered the long-term effects of these techniques. Now that several children born after ART have reached adolescence, it is useful to study the possible long-term consequences of this procedure, such as cancer incidence.…”
mentioning
confidence: 99%
“…Some of the complications have been attributed to a higher frequency of multiple births and to the increased risk of premature delivery; however, other reports indicate that also singleton IVF children have a greater risk of low birth weight and of congenital anomalies [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The empirical evidences are variable and therefore should be considerably evaluated. Some studies suggested that there were potential difficulties for these children, such as genetic disorders, congenital malformations, preterm delivery, low birth weight and perinatal complications, developmental delays and disabilities, and behavioral and mental health difficulties (1,2,(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the available findings suggest that there is a higher overall risk of CP in the population of children born after ART due to multiple births, preterm (<37 weeks of gestation) and very preterm (<32 weeks of gestation) delivery, low (<2500 g) or very low birth weight (<1500 g) (16)(17)(18)(19)(20). Also, these risk factors are strongly associated with numerous long-term health consequences, admission to neonatal intensive care units and prolonged hospitalization (11,(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%